Examination of the Causes and Frequency of Fire Hazard in Communities Housing Refinery Flammable Facilities: A Case Study of PHRC - Nkeleme Emmanuel Ifeanyichukwu; Achigbu Onyemaeze Ikenna; Chukwudi Stanley Ozoh; Edom Ikenna Ellis; Adeyemo Adebisi Fatai (Archives of Current Research International, 2021)
Fire hazards regardless of their immediate or remote cause(s), always have very serious consequences whenever they occur. This paper examines the causes and frequency of fire hazards in the host communities of Port Harcourt Refinery Company (PHRC) flammable materials, to establish the causes and frequency of fire outbreaks in such facilities as the Crudeoil tanks, Crude Distillation Unit (CDU), Fluid Catalytic Cracking Unit (FCCU), Naphtha Hydrotreating Unit (NHU), and suggesting measures to reduce such practices. The research was sorted via an intensive literature review alongside the administration of a well-structured questionnaire. A total of seventy questionnaires with sixty returned adequately filled giving a percentage response of 85.7%. The responses were analyzed using computer-based software (SPSS) and the result was presented in percentages and Relative Importance Indices (RII). The result showed among others that the reoccurring communal practice around PHRC that lead to fire hazard is bush burning (RII=0.91). Other common practices that lead to fire hazards are; Arson and incineration of refuse at proximity to combustible elements. The result also shows that there is no fire enlightenment within this environment. Thus, based on the findings the following are recommended; regulation and supervisory committees be set up and empowered to guide against the act of bush burning around PHRC flammable facilities. Fire prevention measures and enlightenment should be organized within the communities surrounding PHRC, and also the point where PHRC flammable facilities are stored or located within the communities should be well designated so that people can easily see and consequently avoid any activity that can instigate the eruption of fire outbreak.